Cycling power profile characteristics of national-level junior triathletes - Stevens, C. J.; Bennett, K. J. M.; Novak, A. R.; Kittel, A. B.; Dascombe, B. J. (The Journal of Strength and Conditioning Research, 2019)
With the draft-legal rule recently introduced to junior triathlon competition, it has become difficult to assess cycling performance through race results. Therefore, this study assessed the cycling power profile characteristics of national-level junior triathletes to assist with physical assessment and program design. Thirteen male (17.0 ± 1.0 years) and 11 female (17.2 ± 1.3 years) national-level junior triathletes completed a cycling power profile that consisted of maximal intervals that lasted 6, 15, 30, 60, 240, and 600 seconds in duration. Each power profile was completed on a LeMond ergometer using the subject's own bicycle, with power output and cadence recorded for all intervals. Mean power output values for males (783 ± 134, 768 ± 118, 609 ± 101, 470 ± 65, 323 ± 38, and 287 ± 34 W) were significantly (p = 0.05) higher than those for females (554 ± 92, 510 ± 89, 437 ± 75, 349 ± 56, 248 ± 39, and 214 ± 37 W) across all intervals, respectively. Peak power output values for males across the 6- and 15-second intervals (1,011 ± 178 and 962 ± 170 W) were also significantly higher than those for females (674 ± 116 and 624 ± 114 W), respectively (p = 0.05). Developing junior triathletes should aim to increase their capacity across the power profile above the mean values listed. Athletes should further aim to have power outputs equal to that of the best performers and beyond to ensure that they can meet the demands of any competition situation.